2011
DOI: 10.1089/end.2010.0374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of the Memokath Stent as a Second-Line Procedure After Sphincterotomy Failure

Abstract: According to our data, the Memokath stent is not only an alternative treatment option to sphincterotomy, but it is a safe and successful second-line treatment after sphincterotomy failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Urethral stents can serve as a therapeutic alternative to sphincterotomy both as a primary procedure or to treat a failed sphincterotomy procedure [72]. By strict avoidance of putting the stent through the bladder neck, the incidence of stent encrustation and development of dysreflexia can be minimized.…”
Section: Surgical Interventions For Neurogenic Bladdermentioning
confidence: 99%
“…Urethral stents can serve as a therapeutic alternative to sphincterotomy both as a primary procedure or to treat a failed sphincterotomy procedure [72]. By strict avoidance of putting the stent through the bladder neck, the incidence of stent encrustation and development of dysreflexia can be minimized.…”
Section: Surgical Interventions For Neurogenic Bladdermentioning
confidence: 99%
“…A therapeutic alternative to intrasphincteric BoNT-A injections long-term are urethral sphincter stents. Pannek et al showed their safety and feasibility in patients with SCI after failed surgical sphincterotomy [24], but this method is associated with complications such as stent dislocation or stent stenosis [25,26]. However, evidence for treatment efficacy regarding urethral sphincter stents in patients such as in our cohort is lacking as well.…”
Section: Findings In the Context Of The Existing Literaturementioning
confidence: 81%
“…Our results also agreed with those of Pannek et al who noted zero intraoperative complications in their study and did not find significant encrustation, and they postulated that this finding may be because of the stent observation period (13 months). Even in the subset of patients who had a stent for longer periods, they did not encounter encrustation [20]. However, removal was easy, taking about 15 minutes by flushing the stent with cool water < 10°C, which alters the spiral so it becomes soft and pliable in order to facilitate transurethral removal such as that done in the study by Neil et al in which removal took an average of 11 minutes.…”
Section: Discussionmentioning
confidence: 99%